The taxonomic history of Indo-Papuan groundsnakes, genus Stegonotus Duméril et al., 1854 (Colubridae), with some taxonomic revisions and the designation of a neotype for S. parvus (Meyer, 1874) - Kaiser, Christine M.; Kaiser, Hinrich; O’shea, Mark (Zootaxa, 2018)
Since its conceptualization in 1854, 29 species of the colubrid genus Stegonotus have been recognized or described, of which 15 (admiraltiensis, batjanensis, borneensis, cucullatus, derooijae, diehli, florensis, guentheri, iridis, heterurus, melanolabiatus, modestus, muelleri, parvus, poechi) are still considered valid today. Original species descriptions for the members of this genus were published in Dutch, English, French, German, and Italian and, perhaps as a consequence of these polyglot origins, there has been a considerable amount of confusion over which species names should be applied to which populations of Stegonotus throughout its range across Borneo, the Philippines, Wallacea, New Guinea, Australia, and associated archipelagos. In addition, the terminology used to notate characteristics in the descriptions of these forms was not uniform and may have added to the taxonomic confusion. In this paper, we trace in detail the history of the type specimens, the species, and the synonyms currently associated with the genus Stegonotus and provide a basic, species-specific listing of their characteristics, derived from our examination of over 1500 museum specimens. Based on our data, we are able to limit the distribution of S. modestus to the islands of Ambon, Buru, and Seram in the central Moluccas of Indonesian Wallacea. We correct the type locality of S. cucullatus to the Manokwari area on the Bird’s Head Peninsula of West Papua, Indonesian New Guinea and designate a neotype for S. parvus, a species likely to be a regional endemic in the Schouten Archipelago of Cenderawasih Bay (formerly Geelvink Bay), Indonesian New Guinea. We unequivocally identify and explain the problematic localities of the type specimens of S. muelleri and Lycodon muelleri, which currently reside in the same specimen jar. We remove L. aruensis and L. lividum from the synonymy of S. modestus and recognize them as S. aruensis n. comb. and S. lividus n. comb., respectively. We remove S. keyensis and Zamenophis australis from the synonymy of S. cucullatus and recognize them as S. keyensis n. comb. and S. australis n. comb., respectively. We further remove S. reticulatus from the synonymy of S. cucullatus, S. dorsalis from the synonymy of S. diehli, and S. sutteri from the synonymy of S. florensis. We designate lectotypes for S. guentheri, S. heterurus, S. lividus, and S. reticulatus. Lastly, we introduce S. poechi, a valid species not mentioned in the scientific literature since its description in 1924. This brings the diversity in the genus Stegonotus to 22 species. We also caution that in a complex group of organisms like Stegonotus any rush to taxonomic judgment on the basis of molecular and incomplete morphological data sets may perpetuate errors and introduce incongruities. Only through the careful work of connecting type material with museum specimens and molecular data can the taxonomy and nomenclature of complex taxa be stabilized.